Primary Health Care: An Approach to Community Control of Genetic and Congenital Disorders - H Aghajani; A Samavat; M Haghazali; F Valizadeh; G Sarbazi (Tehran University of Medical Sciences, 2009)
In Iran, Primary Health care (PHC) has been a main approach to control of communicable diseases over past thirty years. This approach drastically improved main health indices including Infant Mortality Rate (IMR) in Iran. The experience has had two main impacts on the health situation of the country. Firstly community control of health burden of communicable diseases and secondly, bringing about opportunities to non-communicable diseases including genetic disorders to emerge. Past three decades have been also a determining era for profound progress in basic genetic knowledge and development of community tools for prevention and control of genetic and congenital disorders in the world. These advances will widen the gaps between developing countries that are already lacking of basic genetic knowledge and technologies and developed countries that own these capacities, unless there are clever designing to employ the opportunities to bridge the gaps. Iran has enjoyed its first experience of using community tools for control of one of its prevalent genetic health problem, thalassemia major, adopting primary health care approach.  This article explains the expansion of the concept and the approach to community control of genetic and congenital disorders and that, how this concept is leading the country to fill the gap of genetic knowledge.